2010
DOI: 10.1208/s12249-010-9472-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Effect of Strongly and Weakly Cationic Exchange Resins on Matrix Physical Properties and the Controlled Release of Diphenhydramine Hydrochloride from Matrices

Abstract: Abstract. This study focused on investigating and comparing between the effect of the strongly cationic exchange resin, Dowex 88 (Dow88), and the weakly cationic exchange resin, Amberlite IRP64 (Am64), on the physical properties of matrices and their drug release profiles. The matrices were prepared by direct compression of Methocel K4M (HPMC) or Ethocel 7FP (EC) polymeric matrix formers and contained diphenhydramine hydrochloride as a model drug. The addition of Dow88 to the matrices decreased matrix hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Therefore some fractures could occur on the hollow parts of the resin surfaces (Figure 2E). It is reported that these fractures has no effect on the ion-exchange mechanism [22,26]. Figure 2F shows the surface of ATN-DW complex.…”
Section: Morphological Characterization Of By Semmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore some fractures could occur on the hollow parts of the resin surfaces (Figure 2E). It is reported that these fractures has no effect on the ion-exchange mechanism [22,26]. Figure 2F shows the surface of ATN-DW complex.…”
Section: Morphological Characterization Of By Semmentioning
confidence: 96%
“…Therefore a higher wet size and swelling occurs. This high swelling due to the increased amount of sulfonic acid group not only affects the loading but also causes a sustained/prolonged release [26].…”
Section: Particle Size and Distributionmentioning
confidence: 99%